SPIRIT OF LIFE THROUGH PASSION IN LORD BYRON’S POEMS - Mosleh Habibullah (ELITE JOURNAL, 2019)
Someone who lives in the world cannot escape with enthusiasm. Everyone has passion. the spirit can encourage someone to evaluate what the meaning and value of life is. In this case, it depends on the individual who awakens the spirit to get a better and deeper life value. Emotion becomes the driving force of one's life spirit. Byron was an English poet in the Romantic period, he was born in an abnormal condition at his feet so that his life was very sensitive, his poetry expressed feelings through the power of his emotions and was influenced by his past experiences that were full of suffering throughout his life, he always escaped from it to get a life better with the spirit of his life through a strong desire, to get what he wants and overcome the problems of his life. That is expressed in the three poems in this article.